Development Of Sybr Green I Real-Time Pcr Method For Detection And Differentiation Of Newcastle Disease Virus Pathotypes - Tan, Sheau Wei (2008)

(untitled)
Newcastle disease (ND) which is caused by Newcastle disease virus (NDV) is a highly contagious viral disease of domestic poultry, cage, aviary and wild birds. ND outbreaks have led to substantial losses in the poultry industry. NDV can be classified into three major pathotypes: velogenic, mesogenic and lentogenic. Velogenic strains are highly virulent and may lead to 100% mortality in infected chicken whilst mesogenic and lentogenic strains cause mild clinical or inapparent infections, respectively. Early detection and differentiation of NDV pathotypes are very important during monitoring of suspected ND cases or during disease outbreaks. In this study, SYBR Green I real- time polymerase chain reaction (PCR) was developed for detection and differentiation of NDV pathotypes. Velogenic-specific primers (NDVIF2 & NPV2N) and lentogenic-specific primers (NDVIF2 & NPL2N) were designed to detect specific sequence of velogenic strains and lentogenic/vaccine strains, respectively. After establishing the optimum condition of the real-time PCR, the assay was performed on 22 previously characterized NDV strains. All the velogenic strains were only detected by using velogenic-specific primers (NDVIF2 & NPV2N) with threshold cycle (Ct) ranged from 12.92 to 22.76 and melting temperature between 85.6°C to 86.4°C. Similarly, all the lentogenic/vaccine strains were only successfully detected when lentogenic-specific primers (NDVIF2 & NPL2N) were used. All the lentogenic/vaccine strains amplified with the lentogenic-specific primer had a Ct value ranged from 11.93 to 18.73 and Tm between 87.2°C to 87.6°C. No amplification was found when the NDV velogenic-specific primers and lentogenic-specific primers were used to amplify avian influenza virus (AIV), infectious bronchitis virus (IBV) and infectious bursal disease virus (IBDV). This revealed that both velogenic- and lentogenic-specific primers were pathotype specific and no unrelated viral RNA can be amplified. The newly developed assay had a dynamic detection limit which spans over a 5 log10 concentration range. The velogenic and lentogenic amplifications showed high PCR efficiency of 98.8% and 103%, respectively. Mean coefficient variation (CV) of reproducibility tests for velogenic amplification and lentogenic amplification was around 1% and 2%, respectively. The SYBR Green I real-time PCR was 10-fold more sensitive when compared to the conventional detection method using agarose gel electrophoresis. Turnaround time for the developed assay was approximately 2.5 hours including reverse transcription, PCR amplification and melting curve analysis. Clinical samples from the experimental infected chickens as well as the suspected field cases were collected and then tested on the developed assay. In the experimental infection with lentogenic NDV F strain, virus could be detected 3 days post infection (p.i.), followed by day 4, 5 and 10 p.i. For the SPF chickens infected with high doses of velogenic NDV strain AF2240 (105 to 103 ELD50/0.1 ml), the virus can be detected as early as day 2 p.i., followed by day 3 and 4 p.i. All the infected chickens were dead on day 4 p.i. For the chickens group infected with low doses (102 to 100.5 ELD50/0.1 ml), the virus can be detected starting on day 4 p.i., followed by day 5, 7, 10, 11 and 12 p.i. All the infected chickens were dead on day 12 p.i. The assay was able to detect the viruses as early as day 2 before the observation of clinical signs. This is an important achievement as early detection can prevent further spread of the disease. A total of 41 suspected NDV field cases were tested with the developed assay, 33 cases were NDV negative and 8 cases were positive for velogenic NDV. The results were correlated well with the virus isolation method and F cleavage site sequence analysis. All these 8 isolates possess two pairs of dibasic amino acids at the position 112 to 116 of the F cleavage site, and a phenylalanine residue at the position 117. This F cleavage site analysis revealed that all of the 8 NDV isolates belonged to velogenic group. In the attempt to improve the efficacy of the developed assay, internal amplification control (IAC) was incorporated into the developed real-time PCR assay for detection of PCR inhibitors. The potential of simultaneous detection of IAC and NDV target was investigated. The simultaneous detection was achieved based on the melting curve analysis. The co-amplified products exhibited two distinguished melting peaks at 86.36±0.13°C and 91.42±0.21°C which corresponded to NDV NP gene product and IAC KanR gene product, respectively.In conclusion, this study successfully developed a SYBR Green I real-time PCR for NDV pathotypes detection and differentiation. The virus can be detected directly from clinical samples without the need of virus propagation in chicken embryonated eggs. Owing to these advantages, the developed assay will contribute significantly in the control and prevention of the spread of the disease. ND-infected birds can be rapidly isolated from the healthy bird in the case of field outbreaks, if the causal agent is detected at the early stage of the outbreak. Consequently, spread of the disease and economical losses can be prevented